PERLINDUNGAN HUKUM BAGI PEMBELI LELANG EKSEKUS I HAK TANGGUNGAN DENGAN PARATE EKSEKUS I DI KPKNL PEMATANGS IANTAR ATAS PEMBATALAN PUTUSAN PENGADILAN - Sunggu, Elisa P Op; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
This study discusses the legal protection for buyers auction of mortgage rightsexecution with parate execution at Pematang Siantar KPKNL for cancellation ofcourt decisions. This research is motivated by the fact that the cancellation of a courtdecision on the auction of execution of mortgage rights Article 6 of the Act ofUnderwriting Rights that has been carried out has resulted in an invalid auction andnull and void means that the auctioner's rights to the auction object will end andcertainly cause losses to the auction buyer in good faith who have entrusted themechanism of purchasing goods through an auction facility. The execution of theauction is carried out with the guarantee of the material rights of the mortgagethrough the Pematang Siantar KPKNL. The purpose of writing this thesis, namely;First, to find out the juridical review of the execution of Article 6 of the UnderwritingRights execution, secondly, for legal protection for buyers to auction the execution ofmortgage rights that are canceled based on a court decisionThis type of research can be classified in the type of normative legalresearch, because in this study the authors conducted research by examining librarymaterials. Data sources used are secondary data consisting of primary legalmaterials, secondary legal materials and tertiary legal materials, using descriptivemethods.From the results of the research problem there are three main things thatcan be concluded. First, the execution process for the execution of Article 6 of theUnderwriting Right Law is not yet fully in accordance with the relevant regulations.Second, legal protection for auction buyers is given in a preventive and repressivemanner. Authors' advice, First, the relevant regulations should guarantee legalcertainty for all parties, Second, the Judge who decides the dispute should also payattention to the rights of the auction buyer.Key Words: Legal Protection – Execution Auction – Mortgage Right – ExecutionParate